Genetic inheritance analysis of the resistance to a virulent isolate of Colletotrichum acutatum in strawberry based on an octoploid model = Análisis de la herencia genética de la resistencia a un aislado virulento de Colletotrichum acutatum en frutilla basado en un modelo octoploide - Salazar, Sergio Miguel (2017)
In the present work we propose a hypothesis to explain the mechanism of the genetic control of resistance to anthracnose and we show an experimental model that may support our hypothesis. The inheritance of the strawberry resistance to a virulent strain of Colletotrichum acutatum isolated in Northwestern Argentina was assessed with a progeny obtained from the cross between the susceptible cultivar ‘Pájaro’ as female and the resistant cultivar ‘Sweet Charlie’ as male. Infections were carried out under controlled conditions by spraying a conidial suspension on leaves of young plants and lesions were evaluated from days 10-50 after infection. The disease severity ratings (DSR) values exhibited a continuous distribution. We propose a model based on a gene-for-gene interaction in an octoploid genomic background to explain the results. The model assumes that the genetic control of the resistance is determined by different allelic variants of an R-gene. According to this model, results suggest that susceptibility to this isolate is partially dominant over resistance and that the defensive response would be modulated by the allele dosage, although other gene interactions may also be involved.